Is critique secular?: blasphemy, injury, and free speech - Mahmood, Sara; Asad, Talal (The Townsend papers in the humanities, 2009)
Introduction / Wendy Brown -- Free speech, blasphemy, and secular criticism / Talal Asad -- Religious reason and secular affect : an incommensurable divide / Saba Mahmood -- The sensibility of critique : response to Asad and Mahmood / Judith Butler -- Reply to Judith Butler / Talal Asad -- Response to Judith Butler / Saba Mahmood